2003
DOI: 10.1002/tea.10096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of knowledge integration activities on students' perception of the earth's crust as a cyclic system

Abstract: Systems thinking is regarded as a high‐order thinking skill required in scientific, technological, and everyday domains. However, little is known about systems thinking in the context of science education. In the current research, students' understanding of the rock cycle system after a learning program was characterized, and the effect of a concluding knowledge integration activity on their systems thinking was studied. Answers to an open‐ended test were interpreted using a systems thinking continuum, ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
1
19

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 14 publications
6
103
1
19
Order By: Relevance
“…However, using 5 composition elements of the rock cycle such as magma, igneous rocks, sediments, sedimentary rocks, metamorphic rocks, final analysis was made on this research. The rock cycle processes derived from previous studies of the Kali et al(2003) were 13, however, these could not be used as a analysis criteria because they included exposed rocks as a composition elements which is different from this research. Therefore, the final analysis was made based on 20 which include all rock cycle processes pre-teachers understand and was repeatedly elicited through a comparative analysis from the data collected in this research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using 5 composition elements of the rock cycle such as magma, igneous rocks, sediments, sedimentary rocks, metamorphic rocks, final analysis was made on this research. The rock cycle processes derived from previous studies of the Kali et al(2003) were 13, however, these could not be used as a analysis criteria because they included exposed rocks as a composition elements which is different from this research. Therefore, the final analysis was made based on 20 which include all rock cycle processes pre-teachers understand and was repeatedly elicited through a comparative analysis from the data collected in this research.…”
Section: Discussionmentioning
confidence: 99%
“…By interpreting Kali et al(2003)'s prior research which studied the earth system cycle, we extracted composition elements of the rock cycle, and primary analysis was made based on this. Composition elements of the rock cycle extracted from previous studies of the Kali et al(2003) were 6 including magma, igneous rocks, exposed rock, sediments, sedimentary rocks, metamorphic rocks, and these elements worked as analysis criteria.…”
Section: Discussionmentioning
confidence: 99%
“…학교 현장에서 다루고 있는 교과서의 지구온 난화 관련 단원에서는 온실효과와 지구온난화에 대한 구분을 정확하게 제시하지 못해 학생들이 이 두 가 지의 개념을 오인할 가능성을 가지고 있고 대기효과 를 일으키는 온실기체에 대한 설명이나 지구 대기효 과를 알아보기 위한 실험 등도 매우 부족하며, 이를 보완하기 위해 효과적인 지구온난화의 학습에 적용될 수 있는 교수·학습 프로그램이 필요한 실정이다 (국동 식, 2003). 지구 시스템을 구성하는 요소들끼리 상호 작용을 통해 나타나는 지구온난화 현상을 효과적으로 학습하기 위해서는 고등사고 능력인 시스템 사고를 활용한 교육방법이 필요하다 (Ben-zvi-Assaraf and Orion, 2005a, 2005bKali et al, 2003). 특히, 2009 개정 과학과 교육과정을 살펴보면, 지구과학 영 역에서 지구계가 지구과학 영역을 아우르는 개념적인 초점으로 적용되고 있으며, 중학교 1학년 내용에서 "과학 교과에서 다루는 순환계, 생태계, 소화계 등 여 러 가지 계를 학습하여 지구계 및 지구계의 구성 요 소와 특징을 알게 한다.…”
Section: 서 론unclassified
“…Kali et al [4], suggested that the ability of students to deal with such systems is based on their ability to develop a dynamic-cyclic-systemic perception of our planet. Teaching earth systems, then, requires the development of system thinking amongst students.…”
Section: Understanding How Dynamic Systems Workmentioning
confidence: 99%